2005
DOI: 10.1002/j.2161-0045.2005.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Genograms in Career Counseling With Elementary, Middle, and High School Students

Abstract: Genograms have been used successfully in career counseling with adults; however, there has been limited use of genograms in career counseling with elementary, middle, and high school children. This article focuses on the benefits of using genograms and the reasons for them to be integrated into the comprehensive developmental guidance programs used by professional school counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
2
22
0
1
Order By: Relevance
“…These methods should include curriculum development, planning, and delivery, as well as various effective classroom guidance activities for promoting career development. Some activities that have been highlighted in the professional literature include Beale's (2003) restaurant activity that teaches career competencies through pantomime and role play, and Gibson's (2005) recommendation of using career genograms to explore parental expectations and role models that impact career choice. School counselor educators can offer guidance on the process of creating a career education curriculum for classroom guidance by highlighting the role that childhood career development theory plays in understanding the various needs of students over the lifespan.…”
Section: Recommendation #5: Introduce Specific Methods For Deliveringmentioning
confidence: 99%
“…These methods should include curriculum development, planning, and delivery, as well as various effective classroom guidance activities for promoting career development. Some activities that have been highlighted in the professional literature include Beale's (2003) restaurant activity that teaches career competencies through pantomime and role play, and Gibson's (2005) recommendation of using career genograms to explore parental expectations and role models that impact career choice. School counselor educators can offer guidance on the process of creating a career education curriculum for classroom guidance by highlighting the role that childhood career development theory plays in understanding the various needs of students over the lifespan.…”
Section: Recommendation #5: Introduce Specific Methods For Deliveringmentioning
confidence: 99%
“…This visual allows professionals to see generational patterns within family systems (Altshuler, 1999;Dunn & Levitt, 2000;Halevy, 1998;Kuehl, 1995;Magnuson & Shaw;Wiggins-Frame, 2001). Counselors may use genograms to assess career choices (Gibson, 2005), spirituality (Hodge, 2001), culture (Estrada & Haney, 1998;Hardy & Laszloffy, 1995;Watts-Jones, 1997), and solutions (Kuehl, 1995) found in the immediate and extended family. Genograms may foster engagement and rapport between student and counselor (Altshuler, 1999).…”
Section: Genogrammentioning
confidence: 99%
“…It has been shown that career interventions do appear to have some impact on the career awareness and exploratory behaviors of children (Gibson, 2005;Lapan, 2004;Magnuson & Starr, 2000;Schultheiss, 2005;Wood & Kaszubowski, 2008). It has been shown that career interventions do appear to have some impact on the career awareness and exploratory behaviors of children (Gibson, 2005;Lapan, 2004;Magnuson & Starr, 2000;Schultheiss, 2005;Wood & Kaszubowski, 2008).…”
Section: Resultsmentioning
confidence: 99%